Global Burden of Meconium‐Stained Amniotic Fluid: A Systematic Review and Meta‐Analysis of Prevalence With Descriptive Synthesis of Determinants - Shervin Tabrizian; Tiba Mirzarahimi; Mojgan Mirghafourvand; Mahsan Nabighadim (Health Science Reports, 2026)
ABSTRACT Background and Aims Meconium‐stained amniotic fluid (MSAF) is a common intrapartum finding associated with adverse perinatal outcomes. Comprehensive global estimates of its prevalence and determinants are lacking. This systematic review and meta‐analysis aimed to estimate the global pooled prevalence of MSAF and classify its associated factors. Methods We searched Ovid MEDLINE, Scopus, Web of Science, Embase, Cochrane Library, SID, and Google Scholar up to January 1, 2026, for observational studies reporting MSAF prevalence or associated factors. Pooled prevalence with 95% CI was calculated using a random‐effects model with Logit transformation. The Knapp–Hartung adjustment and 95% prediction interval were applied. Heterogeneity was quantified using I 2 . Subgroup analyses and meta‐regression explored heterogeneity sources. Quality was assessed using the Newcastle‐Ottawa Scale. Due to high heterogeneity, meta‐analysis of risk factors was not feasible; findings were summarized descriptively. Results Fifty‐one studies were included (44 for prevalence; 1,414,705 births). The global pooled prevalence was 13.0% (95% CI: 10.8–15.6%; prediction interval: 6.9–23.1%; I 2 = 99.71%). Prevalence doubled in low‐income compared to high‐income countries (22.2% vs. 11.1%; p < 0.001). Significant variations were observed by continent ( p < 0.001), country ( p < 0.001), and meconium consistency ( p = 0.004). Meta‐regression showed a significant positive association with mean gestational age ( β = 0.077, p = 0.014). Twenty‐two risk factors were classified into four domains: Social/Structural (inadequate antenatal care, delayed referral, low income), Intrapartum (prolonged/obstructed labor, PROM, oligohydramnios, non‐reassuring fetal heart rate pattern [NRFHRP]), Maternal (hypertensive disorders, diabetes, anemia), and Fetal/Physiological (advanced gestational age, primiparity, macrosomia). The strongest modifiable determinants were intrapartum factors—NRFHRP (adjusted odds ratio [AOR] up to 21.9), obstructed labor (AOR up to 24.6)—and system‐level barriers, particularly delayed referral (AOR up to 15.3). Intrauterine growth restriction (IUGR) showed no statistically significant association in any adjusted analysis. Conclusion MSAF affects one in eight pregnancies globally, with a higher burden in low‐income settings. Four‐domain classification identifies actionable targets—intrapartum monitoring failures and health‐system barriers—for quality improvement. Meconium consistency grading offers a simple risk stratification tool. Addressing these factors, particularly in resource‐limited settings, can reduce preventable perinatal morbidity and align with global health equity goals.